STAT3 as a potential therapeutic target in ALDH(+) and CD44(+)/CD24(+) stem cell-like pancreatic cancer cells - Lin, Li (Int J Oncol, 2016)
Persistent activation of signal transducers and activators of transcription 3 (STAT3) is commonly detected in many types of cancer including pancreatic cancer. Whether STAT3 is activated in stem cell-like pancreatic cancer cells and the effect of STAT3 inhibition, is still unknown. Flow cytometry was used to isolate pancreatic cancer stem-like cells which are identified by both aldehyde dehydrogenase (ALDH)-positive (ALDH(+)) as well as cluster of differentiation (CD) 44-positive/CD24-positive subpopulations (CD44(+)/CD24(+)). STAT3 activation and the effects of STAT3 inhibition by STAT3 inhibitors, LLL12, FLLL32, and Stattic in ALDH(+) and CD44(+)/CD24(+) cells were examined. Our results showed that ALDH(+) and CD44(+)/CD24(+) pancreatic cancer stem-like cells expressed higher levels of phosphorylated STAT3, an active form of STAT3, compared to ALDH-negative (ALDH(−)) and CD44-negative/CD24-negative (CD44(−)/CD24(−)) pancreatic cancer cells, suggesting that STAT3 is activated in pancreatic cancer stem-like cells. Small molecular STAT3 inhibitors inhibited STAT3 phosphorylation, STAT3 downstream target gene expression, cell viability, and tumorsphere formation in ALDH(+) and CD44(+)/CD24(+) cells. Our results indicate that STAT3 is a novel therapeutic target in pancreatic cancer stem-like cells and inhibition of activated STAT3 in these cells by STAT3 inhibitors may offer an effective treatment for pancreatic cancer.